Pengaruh Faktor Kompensasi Terhadap Kinerja Karyawan Pada PT. Bank Syariah Indonesia Kcp Pangkalan Berandan - DIan, Dian Sabrina; Muhammad Saleh (Jurnal Ekonomi dan Keuangan Syariah, 2022)
This study aims to determine the effect of compensation on the performance of employees of PT. Bank Syariah Indonesia KCP Pangkalan Berandan. The research method used is quantitative research using a simple linear regression method. The sample in this study amounted to 40 respondents using the census method. Data collection used a questionnaire and data processing used the SPSS Statistics Version 24.0 analysis tool. The results showed that compensation has an influence on the performance of employees at PT. Bank Syariah Indonesia KCP Pangkalan Berandan is 12%, while the rest is influenced by other factors outside the variables studied. The results of the study show that compensation is one of the driving factors that can improve employee performance based on the compensation provided by the company to its employees. Compensation is an award or reward for services provided by the company to employees for their contribution to the company. This supports the theory put forward by Handoko (2003) which means that compensation is something that is received by employees as remuneration for their work, so with the provision of compensation it can increase work performance, motivation and job satisfaction and increase employee needs. Compensation is not only important because it is the main motivation for someone to become an employee, but also has a big influence on employee morale and enthusiasm